2007
DOI: 10.1245/s10434-007-9733-9
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Ablation After Radiofrequency Ablation of Hepatocellular Carcinoma: Analysis of Risk Factors and Prognostic Factors

Abstract: This study demonstrated that incomplete ablation after RFA of HCC was associated with tumor size > 3 cm. Our data also suggest that aggressive further treatment of tumors with incomplete ablation aiming at complete tumor response improves overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 47 publications
4
51
3
Order By: Relevance
“…For example, Lam et al . prospectively treated 298 HCC patients using RFA and demonstrated a significantly shorter survival time for 25 patients whose tumors had been incompletely ablated33.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lam et al . prospectively treated 298 HCC patients using RFA and demonstrated a significantly shorter survival time for 25 patients whose tumors had been incompletely ablated33.…”
Section: Discussionmentioning
confidence: 99%
“…This observation confirms other reports in literature in which the size and location near major vessels are factors associated with higher local recurrence rate. 26,27 A potential limitation of this study is the reduction of sample size after matching that can affect the accuracy of survival-estimated values. However, the one-to-one propensity matching technique allows to obtain highly selected samples that significantly improve the quality of univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…5,[20][21][22][23][24][25][26][27] Surprisingly, a histological study in patients who underwent liver transplantation after an RFA procedure revealed residual tumor tissue in 37% and 71% of patients with HCC 3 cm and HCC >3 cm, respectively. 28 The combination with TACE is expected to reduce such microscopic local tumor progression.…”
Section: Discussionmentioning
confidence: 99%